The Impact of PKH Social Assistance on Poverty Levels in Lampung Province: An Interrupted Time Series Analysis - M. Ikhsan Nur Rozak; Asih Murwiati (Transpublika Publisher, 2025)
Poverty remains a persistent development challenge in Indonesia, particularly in regions such as Lampung Province. This study aims to analyze the impact of the Family Hope Program (PKH) on poverty levels in Lampung Province. The study uses a quasi-experimental approach through the Interrupted Time Series (ITS) method with annual time series data for the period 2001–2024. The dependent variable in this study is the poverty level, while the independent variables representing the policy intervention are the intervention dummy and the post-intervention trend. In addition, the study also includes real Gross Regional Domestic Product (GRDP) per capita and inflation as control variables. The model is estimated using the Ordinary Least Squares (OLS) method. The results show that the time trend has a negative and significant effect on the poverty level. PKH implementation has an immediate impact on reducing poverty levels in the period after the intervention. However, changes in poverty trends after policy implementation do not show a significant effect. Real GRDP per capita is proven to have a negative and significant effect on poverty levels, while inflation has no significant effect. These findings indicate that social assistance plays a role in reducing poverty, especially in the short term, while economic growth remains an important factor in sustainable poverty reduction.